Curcuminoids and ω-3 fatty acids with anti-oxidants potentiate cytotoxicity of natural killer cells against pancreatic ductal adenocarcinoma cells and inhibit interferon γ production - Fiala, Milan; Halder, Ramesh; Almasi, Anasheh; Sagong, Bien; Leung, Jessica; Jewett, Anahid (Frontiers in Physiology, 2015)
Pancreatic cancer has a poor prognosis attributed in part to immune suppression and deactivation of natural killer (NK) cells. Curcuminoids have a potential for improving the therapy of pancreatic cancer given promising results in cancer models and a clinical trial, but their oral absorption is limited. Our objective in this study is to show curcuminoid anti-oncogenic effects alone and together with human NK cells. We tested curcuminoids in an emulsion of ω-3 fatty acids and anti-oxidants (“Smartfish”) regarding their direct cytocidal effect and enhancement of the cytocidal activity of NK cells in pancreatic ductal adenocarcinoma (PDAC) cells (Mia Paca 2 and L3.6). Curcuminoids (at ≥10 μM) with ω-3 fatty acids and anti-oxidants or with the lipidic mediator resolvin D1 (RvD1) (26 nM) induced high caspase-3 activity in PDAC cells. Importantly, curcuminoids with ω-3 fatty acids and anti-oxidants or with RvD1 significantly potentiated NK cell cytocidal function and protected them against degradation. In a co-culture of cancer cells with NK cells, interferon-γ (IFN-γ) production by NK cells was not altered by ω-3 fatty acids with anti-oxidants or by RvD1 but was inhibited by curcuminoids. The inhibition was not eliminated by ω-3 fatty acids or RvD1 but was relieved by removing curcuminoids after adding NK cells. In conclusion, curcuminoids with ω-3 fatty acids and anti-oxidants or with RvD1 have increased cytotoxic activity on PDAC cells alone and with NK cells. The effects of curcuminoids with ω-3 fatty acids and anti-oxidants on pancreatic cancer will be investigated in a mouse model with humanized immune system.